Variasi Aksen dan Leksem Dialek Arab: (Kajian Sosiodialektologi pada Dialek Libya Timur dan Barat) - Wildana Wargadinata; Syifa Rifani; Arina Haque (Alfaz (Arabic Literatures for Academic Zealots), 2021)
The research aims: (1) to describe the differences in accent and lexeme variations in the eastern and western Libyan dialects; and (2) to describe the social factors of Libyan society that cause dialect variations. The method used is descriptive qualitative with data sources from interviews with native Libyan speakers. Direct interviews carried out the data collection technique. The results of this study are: (1) Libyan dialect variations between the Eastern and Western Libyan dialects are divided into accent and lexeme variations. The researcher found three different accent variations of the two dialects. The differences in accent include phonetic differences with accelerations and changes in pronunciation. Meanwhile, in the lexeme, researchers found 20 variations of the lexeme. These variations include onomasiological symptoms in most of the vocabulary and semasiological symptoms in some of the lexemes; (2) The factors causing the emergence of dialect variations are: The influence of geographic location; The social condition of the Libyan people; The tradition of settling down and being close to the family after marriage; The society that divided was considered a disgrace. Meanwhile, two factors influence the similarity between the Libyan dialect and Fushah Arabic, namely: the Libyan dialect Lexem can be derived from the Fushah language; The Libyan dialect axon is a Fushah language experiencing affixes and accelerations in pronunciation.